MIRACLE THAT WAS TAKEN: REFLECTIONS ON EX-VOTIVE LETTERS AND TICKETS FOR HEALTH (Revista Internacional de Folkcomunicação, 2024)
The genesis of the term ex-votos dates to the Greek and Roman people and brings in its semantics the recognition of faith, being materialized in pieces that symbolize gratitude for a grace achieved, in many cases referring to the cure of an illness. Ex-votos can present themselves in different ways, however, this article aims to analyze some aspects of the ex-votive letters and notes researched through the Ex-votos do Brasil project, which aims to identify and catalog the vast typology of Brazilian ex-votos. The focus here is justified by bringing elements arising from a Folkcommunicational and linguistic process, with theoretical bases that substantiate the importance and strength that the ex-voto has with the media.